Lessons from psychiatry and psychiatric education for medical learners and teachers. (June 2013) - Hilty, Donald M.; Srinivasan, Malathi; Xiong, Glen L.; Ferranti, Jessica; Li, Su-Ting T.
Abstract: Medical learners, teachers, and institutions face significant challenges in health care delivery and in training the next generation of clinicians. We propose that psychiatry offers lessons which may help improve how we take care of patients and how we teach others to care for patients. Our objective is to discuss what learners and teachers can learn from psychiatry, organized around (1) how we make decisions, (2) how we learn, and (3) how we reflect on our practice. Information from clinical care, education, neuroscience and other aspects of life (e.g. business, creativity, and research) help us on these processes. We make 'good' decisions in concert with patients and learners, by listening to their experiences, asking questions and exploring subjective and objective information. Our learning has a neurobiological basis, and is effectively furthered by personalization, reinforcement, acquisition of critical thinking skills, and assessment of our limitations and errors. Our ability to reflect is determined by attitude, skill, tolerating ambiguity or dissonance, and planning for the unexpected. These processes – in addition to knowledge and other skills – will help physicians be successful in practice, learning and teaching, research and leadership.